2017
DOI: 10.1111/apt.14342
|View full text |Cite
|
Sign up to set email alerts
|

Survival after treatment with curative intent for hepatocellular carcinoma among patients with vs without non‐alcoholic fatty liver disease

Abstract: Patients with NAFLD-HCC had worse survival after OLT but favourable survival after resection, particularly in the absence of cirrhosis, as compared with non-NAFLD-HCC aetiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 33 publications
(64 reference statements)
9
45
0
2
Order By: Relevance
“…Non‐cirrhotic patients with HCC presented at older age and with larger and more advanced HCC that was more often outside the Milan criteria, consistent with other studies . The significant difference in tumour size is probably due to the lack of HCC surveillance in the majority of patients with non‐cirrhotic HCC, who were not known to have underlying liver disease prior to the HCC presentation.…”
Section: Discussionsupporting
confidence: 87%
“…Non‐cirrhotic patients with HCC presented at older age and with larger and more advanced HCC that was more often outside the Milan criteria, consistent with other studies . The significant difference in tumour size is probably due to the lack of HCC surveillance in the majority of patients with non‐cirrhotic HCC, who were not known to have underlying liver disease prior to the HCC presentation.…”
Section: Discussionsupporting
confidence: 87%
“…This important finding suggests a need to reframe our understanding of the NASH‐HCC association to ensure that effective surveillance measures are instituted. The poorer outcomes both pre‐ and post‐transplantation in this patient population, where tumours are often discovered at a more advanced stage with larger volume and greater degrees of infiltration and in the presence of diabetes and obesity, only further underscores the need for improved HCC screening. Consequently, outcomes for NASH‐associated HCC are, in general, inferior to other aetiologies of liver disease as lower survival rates and higher 1‐year mortality rates after diagnosis of HCC have been reported .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the majority of NASH patients with HCC die from their primary liver cancer rather than from cardiovascular disease, and rates of HCC‐related mortality are greatest in the NASH population . On the other hand, survival rates for surgical resection in patients with NASH and HCC are similar to other liver diseases, particularly in the absence of cirrhosis, albeit in highly selected surgical candidates …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the complications recorded in this study were those observed when patients were admitted to clinics. The prolonged enrolment period and a major hepatitis B virus infection in our study could be additional sources of bias since survival varied among HCC patients with different aetiologies …”
Section: Discussionmentioning
confidence: 99%